Beyond Privacy and Passing-Off: Designing India’s Comprehensive AI-Era Personality Rights (Maharaja Surajmal Institute Law Journal, 2026)
Human society has long celebrated individual talent through public figures—actors, athletes, musicians, writers, and digital influencers—whose identities evolve into commercially valuable brands. Their names, images, voices, and mannerisms possess significant economic worth, giving rise to personality rights (also known as publicity rights), which enable individuals to control and monetize the commercial use of their persona. These rights recognize identity as a valuable intangible asset that must be protected from unauthorized exploitation. In India, personality rights are not codified but are instead protected through a frag mented legal framework, including passing-off under trademark law, defamation under the Bhartiya Nyaya Sanhita, 2023, and the right to privacy under Article 21 of the Constitution. However, rapid technological advancements, particularly in artificial intelligence, have exposed critical gaps in this framework. AI-driven tools can now create deepfakes, replicate voices, generate digital avatars, and simulate real individu als at scale, enabling widespread misuse across social media, advertising, and political communication, often without clear accountability or effective remedies. This paper undertakes a comparative doctrinal analysis to examine the status and lim itations of personality rights in India. It distinguishes between the proprietary nature of publicity rights and the personal dimension of privacy rights, and evaluates approaches adopted in jurisdictions such as the United States, United Kingdom, European Union, Japan, and Brazil. By identifying regulatory shortcomings and emerging risks, the study highlights the urgent need for a coherent and robust legal framework in India to safe guard personality rights in the digital era.
Keywords: trademark law, substantial economic value, jurisdictions